Histopathological spectrum of primordial odontogenic tumor with co-existing dentigerous cyst: 1st reported case of the world with a proposed 'updated diagnostic criteria' - Dhara Dwivedi; Nitin Prabhakar; Monal Yuwanati; Gunjan S. Aswal; Renu Rawat (BMC, 2024)
Abstract Background POT is a relatively newly described benign odontogenic tumor with very few cases registered to date. We present the 1st case of Primordial odontogenic tumor (POT) from Sub-Saharan Africa with unique clinicopathological features; also, this is the first case to report POT's existence as a Hybrid Odontogenic lesion (HOL), with a pertinent review of the literature. Case presentation This was a 17-year-old patient who presented with slow-growing, painless posterior mandibular swelling. The imaging revealed a well-defined, unilocular, expansile, lytic lesion with internal calcific foci surrounding an impacted #36, indicating a calcifying odontogenic cyst. The incisional biopsy revealed the presence of POT. The tumor was excised along with the involved tooth. Conclusion POT is predominantly a non-aggressive and mostly affects the pediatric population. Hence, clinicians must be updated on all the aspects of this tumor to diagnose it appropriately and avoid any undue over-or under-treatment.